Japan's great stagnation : financial and monetary policy lessons for advanced economies - Hutchison, Michael M.; Westermann, Frank, 1970- (CESifo seminar series., 2006)
Experts on the Japanese economy examine Japan's prolonged period of economic underperformance, analyzing the ways in which the financial system, monetary policy, and international financial factors contributed to its onset and duration.